1983
DOI: 10.1039/c39830000192
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of acetate-derived oxygens in the tetronic acids of Penicillium multicolor

Abstract: Incorporation of sodium [I -l3C, '802]acetate by Penicillium multicolor into multicoianic, multicolic, and multicolosic acids, (I), ( 2 ) , and (3), respectively, has given samples which when derivatised and examined by spin echo Fourier transform (S.E. F.T.) 3C n.m.r. spectroscopy show 80-induced l3C-satellites, confirming the previously proposed biosynthetic pathway involving oxidative fission of the P-ketide derived intermediate 6-pentylresorcylate ( 8 ) and establishing that lactonisation of the tetronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…(Kasettrathat et al, 2008), vulpinic acid and pinastric acid by Tuckermannopsis pinastri (Golojuch and Lawrey, 1988), penicillic acid by Penicillium cyclopium and viridicatic acid by Penicillium viridicatum (Gedge and Pattenden, 1979). Labelling studies suggested that multicolosic acid is a polyketide synthesised by oxidative cleavage of an aromatic precursor 6-pentylresorcylate (Holker et al, 1983(Holker et al, , 1987. Multicolanic acid and related derivatives have also been classified as hexaketides because of their polyketide origin (Turner and Aldridge, 1983).…”
Section: Production Of -Butyrolactonementioning
confidence: 97%
See 1 more Smart Citation
“…(Kasettrathat et al, 2008), vulpinic acid and pinastric acid by Tuckermannopsis pinastri (Golojuch and Lawrey, 1988), penicillic acid by Penicillium cyclopium and viridicatic acid by Penicillium viridicatum (Gedge and Pattenden, 1979). Labelling studies suggested that multicolosic acid is a polyketide synthesised by oxidative cleavage of an aromatic precursor 6-pentylresorcylate (Holker et al, 1983(Holker et al, , 1987. Multicolanic acid and related derivatives have also been classified as hexaketides because of their polyketide origin (Turner and Aldridge, 1983).…”
Section: Production Of -Butyrolactonementioning
confidence: 97%
“…5). Labelling studies have suggested that multicolosic acid and related derivatives are synthesised by oxidative cleavage of an aromatic precursor 6-pentylresorcylate (Holker et al, 1983(Holker et al, , 1987. Therefore, it is unlikely that 4-hydroxybutyric acid lactone will act as a precursor for the synthesis of methyl-O-methylmulticolate acetate.…”
Section: Quorum Sensing System Restorationmentioning
confidence: 98%
“…Such a stereocontrol, in a sense, mimics the biogenetic route of naturally occurring 5-ylidene-2(5H)-furanones, in which the covalent bond fixes the E-geometry. 15 Scheme 5 4. Radical-and cation-mediated ring expansion of 4-hydroxy-2cyclobutenones to 2-(5H)-furanone/4-cyclopentene-1,3-dione Four-to five-membered ring expansion occurs not only via thermal/ photochemical (above) and catalyzed (with transition-metal) rearrangements, but also by those via reactive intermediates, which should expand the synthetic utility of 1 as a C 4 -synthon.…”
Section: Methodsmentioning
confidence: 99%
“…In the reactions of 2-4 with allylsilanes and silyl enol ethers, a more congested reaction site caused deviation from the 1,2 to the 1,4 mode (entries 2, 4,11,13,18). The reaction with silyl ketene acetals gave a 1,2-adduct with TiCl 4 and a 1,4-adduct with ZnCl 2 , regardless of the substitution pattern of the organosilanes (entries 6-9, 14, 15,19); competitive formation of a titanate intermediate, prior to addition, may change the course of the reaction. The reaction of diester 5 occurred only with a silyl enol ether and a silyl ketene acetal according to a 1,4-addition (entries 20, 21).…”
Section: Lewis-acid Catalyzed Reaction Of Squaric Acid Systems With Unsaturated Organosilanesmentioning
confidence: 99%
“…However for the C-3 resonance, three isotopically shifted signals appeared due to species having 1 8 0 in (a) the singly-bonded oxygen, (b) the doubly-bonded oxygen, and mainly (c) both the singly and doubly-bonded oxygens. 5 Since the resonances corresponding to (a) and (b) probably result from residual 1 6 0 2 in the fermentation, both oxygen atoms of the spiro-lactone are added by oxidative processes, in agreement with observations for andibenin B.6 In the aliphatic region the resonances due to C-4, C-11, C-3', and C-5' all show isotope shifts which complement those observed in the carbonyl region, thereby accounting for all five ' 8 0 atoms incorporated into austin. Interestingly, C-6' also has a shifted signal (Table 1).…”
mentioning
confidence: 99%